(3OjhGf GHf GdeYJRs - (3YHO Gddg Hf eMeO GdeYJR HGddg Hf GdeJhcd Hf GdeYJUe Hf GdQTjO GdYHGSj, GHf GdeYJR, CHh GdYHGS,J (B296 (3g` s
(3ChdgG (B:s
(3bGd CHhGdYHGS aj GdaNQ Ydi bGajI GdCda(B: (3hSGQjI dG Jed GdHcG LQi OeYgG aj NOhO GdKQi s
(3BNQgG (B:s
(3CdG jG faS Ef JQVj HbhJ aCfJ YRjRI CHOG ZfjI OYj Yfc GdeWGeY hGdCeGfj ace CefjI LdHJ efjI JeJ bGajI GdjGA aj GdRgO HYhf Gddg s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B154 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B443s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B209 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs